Epidemiological and Pathogenic Characteristics of Benign and Malignant Thyroid Nodules Undergoing Ultrasonography for Health Checkup Population - Yao Z; Zhou W; Shen Z; Li Q (International Journal of General Medicine, 2025)
Zhifeng Yao, Weihong Zhou, Zhixiang Shen, Qingxia Li Department of Health Management Center, Nanjing Drum Tower Hospital, Affiliated Hospital of Medical School, Nanjing University, Nanjing, Jiangsu, People’s Republic of ChinaCorrespondence: Qingxia Li, Department of Health Management Center, Nanjing Drum Tower Hospital, Affiliated Hospital of Medical School, Nanjing University, No. 321, Zhongshan Road, Gulou District, Nanjing, Jiangsu, 210008, People’s Republic of China, Tel +8615996301027, Email liqingxia0203@126.comPurpose: To analyze the epidemiological and pathogenic characteristics of benign and malignant thyroid nodules undergoing ultrasonography for health checkup population and evaluate the value of ultrasonography in early detection of thyroid cancer.Methods: The thyroid nodules ultrasonic characteristics of 70430 examinees in different ages and genders were retrospectively analyzed according to the Chinese Thyroid Imaging Reporting and Data System (C-TIRADS). The high-risk thyroid nodules pathological results were compared with ultrasonic C-TIRADS to analyze the value of ultrasonography in early detection of thyroid cancer.Results: The total thyroid nodules prevalence was 47.64%. Females had a significantly higher prevalence of thyroid nodules than males (52.10% vs 43.48%; P < 0.01), and thyroid nodules prevalence was gradually increased with age (P for trend < 0.01). Thyroid nodules were mainly multiple, unilateral lobe, maximum diameter < 1cm and solid nodules. The distribution of thyroid nodules in different genders was different in number, location, maximum diameter, echo characteristics and C-TIRADS (P < 0.01). The distribution of C-TIRADS in different ages was statistically different (P < 0.01). The thyroid nodules prevalence of C-TIRADS 2, 3, 4A, 4B, 4C, and 5 were 12.88%, 32.04%, 2.33%, 0.36%, 0.02% and 0.009%, respectively (P < 0.01). A total of 436 examinees were definitely diagnosed, of which 323 were benign and 113 were malignant, and the difference in the prevalence of malignancies among different C-TIRADS was statistically significant (P < 0.01). Well-differentiated papillary thyroid cancer accounted for 86.73% and most were early stage cancer and micro-carcinoma. The sensitivity, specificity and accuracy of ultrasonic C-TIRADS diagnosis of thyroid cancer were 84.07%, 97.41%, and 97.39%, respectively.Conclusion: Age and gender are closely related to thyroid nodules prevalence. Ultrasonography based on C-TIRADS has certain value in detecting thyroid nodules and screening early thyroid cancer.Keywords: thyroid nodules, ultrasonography, epidemiology, C-TIRADS, screening